“Radical Reorganization…”: M. I. Pyrohov as Trustee (1858–1861) and Measures in Improving Professionalism of Teachers of Kyiv Educational District - Oksana Drach (Київські історичні студії)
Reformation of the educational system of independent Ukraine encourages the study of concrete experience of implementing radical changes in the field of education. The purpose of the article is to study the innovations of the trustee of the Kyiv Educational District M. I. Pyrohov in teacher training in the state. The methodological basis of the study is the socio-cultural approach in combination with psychohistory. As a result of the study it is proved that the authoritative doctor and scientist M. I. Pyrohov in Kyiv Educational District continued the mission of “serving the truth and the Motherland”. Progressive pedagogy, sincere humanism and democracy in the educational process became the core of the trustee’s administrative activity. The personality of a teacher was in the focus of change. The trustee implemented measures to improve the professionalism of the teaching staff in the District: projects of the Pedagogical Seminary and a special Pedagogical Gymnasium were prepared; training of university students in didactics was improved and their practical classes were organized on the basis of the Kyiv gymnasiums; the concept of pedagogical courses at provincial gymnasiums for training of teachers of the county and parish schools was offered; competitive procedure for appointing teachers; educational and methodical meetings of pedagogical councils were initiated. The strategy of innovations was to increase the pedagogical authority and personal dignity of teachers.We believe that under Pyrohov as the trustee there was an irreversible turn towards true democratization of the management system, relations between the subjects of the educational process, modernization of didactic and pedagogical technologies in the Kyiv Educational District. The success of innovations was due to the high public authority of Pirogov, his exceptional professionalism and integrity as an administrator, a sincere desire for the progress of education in the state.